Green function approach to the theory of superconductivity in the t - J model - Plakida, N.M. (Condensed Matter Physics, 1998)
The theory of superconducting pairing due to the exchange and kinematical interactions in the t - J model in a paramagnetic state is developed. The Dyson equation for the matrix Green functions in terms of the Hubbard operators is obtained in the noncrossing approximation. The linearized self-сonsistent system of Eliashberg equations is proposed to study the temperature and doping dependence of the quasi-particle hole spectrum in the normal state and to calculate the temperature of the superconducting phase transition and the symmetry of the gap function.